A generalized charge transfer model in the description of Anna’s diodes - Мельніков, Є. В.; Мельніков, Д. Є. (Proceedings of National Aviation University (archive), 2021)
The application of the model of an inertial element whose nonlinearity is given by the dependence of the parameters on charge is considered for the description of the processes occurring in the Hann diodes as solid-state devices of a super-high frequency